Tanzanian student nurse-midwives knowledge and skills in the prevention and management of postpartum hemorrhage - Rose Faustine; Michael Johnson Mahande; Jane Rogathi; Eva Christina Furskog Risa; Ingrid Tjoflåt (International Journal of Africa Nursing Sciences, 2024)
Background: Postpartum hemorrhage is the leading cause of maternal mortality in Tanzania. Ensuring quality pre-service education and training competent midwives is crucial to reducing preventable maternal deaths. Aim: The study aims to assess the level of knowledge and skills of student nurse-midwives in preventing and managing postpartum hemorrhage after completing the midwifery module in the diploma program, prior to commencing their clinical practice. Method: A cross-sectional study was conducted at two colleges of health and allied sciences, referred to as Site A and Site B. The study involved 110 student nurse-midwives. Data were collected using structured self-administered questionnaires and skill checklists to assess their knowledge and competencies. Descriptive statistics were summarized using frequencies and proportions. The knowledge and skill scores were classified into three categories: low (<40 %), moderate (40–79.9 %), and high (80–100 %) based on Bloom Techniques. Results: The results revealed that most student nurse-midwives from site A had poor knowledge, while those from site B demonstrated moderate knowledge in the prevention and management of postpartum hemorrhage, with 33 (60 %) and 37(67.3 %) respectively. Additionally, over three-quarters of student nurse-midwives from both site A and B exhibited poor skills in the prevention and management of postpartum hemorrhage, with 50 (90.9 %) and 42 (76.4 %) respectively. Conclusion: The results revealed that the knowledge and skills of student nurse-midwives’ in preventing and managing postpartum hemorrhage are overall not satisfactory. Enhancing their education through active learning, problem-solving, and hands-on skills when dealing with patients with postpartum hemorrhage could produce more competent graduates.